VD_FINDINFO Arrêt / 2010 / 48 vom 17. Dezember 2009 - VD Tribunal cantonal (2009)
INTERDICTION, TUTELLE, MALADIE MENTALE, PRIVATION DE LIBERTÉ À DES FINS D'ASSISTANCE, PROPORTIONNALITÉ | 369 CC, 397a CC, 380 CPC, 393 CPC, 398a CPC, 398d CPC